Multiple Primary Malignancy of Esophageal and Gastric Synchronous and Colon Metachronous - Riki Tenggara; Lauretta Ariella Sugondo (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Multiple primary cancer is an incidence when a patient has multiple malignancy in two or more organs without possibility of metastatic lesion. There have been many reports on mutiple primary cancer since Billroth reported it for the first time in 1879. Patients who have been diagnosed with a cancer have higher risk for developing another cancer, thereby physician and the patients should raise more awareness toward possibility of developing a new metachronous or synchronous cancer. We report a patient who has three histologically distinct cancers. Resected primary colon adenocarcinoma and 3 years after came with hematemesis and diagnosed to have a metachronous squamous cell carcinoma of the oesophagus synchronous with gastric adenocarcinoma. This case is interesting due to the clustering of three primary cancers (synchronous and metachronous) which is a rare occurrence in a single patient.